Contested Coastlines: The Political Economy of Coastal Exclusion and Special Economic Zone Development in Bali - Gede Indra Pramana; Kadek Dwita Apriani; I Ketut Putra Erawan (Politicon : Jurnal Ilmu Politik, 2026)
This study examines the political economy of coastal governance in Bali, focusing on the tension between national Special Economic Zone (SEZ) policies and local community rights. Following the establishment of the Sanur and Kura-Kura SEZs, Bali’s southern coast has undergone rapid state-led transformation. Drawing on the frameworks of environmental politics and the coastal commons, this qualitative case study investigates how centralized development strategies affect local participation and spatial access. Primary data were collected between May and November 2024 through desk research and semi-structured interviews (N=10) with government officials, private-sector developers, and civil society organizations. The findings reveal that local participation is not merely suboptimal but structurally marginalized. In the Kura-Kura SEZ, governance takes the form of spatial enclosure, with corporate identity card systems restricting traditional fishermen's access to the coastal commons. In Sanur, the rapid displacement of coastal traders demonstrates institutional co-optation, using local village elites as intermediaries to enforce compliance and neutralize resistance. Ultimately, this article contributes to environmental political science by conceptualizing SEZs as exclusionary political arenas rather than purely administrative spaces. To prevent further marginalization, the study recommends legally embedding traditional (Adat) representation on SEZ supervisory boards and decentralizing environmental oversight to ensure inclusive and sustainable coastal governance.